Third generation autologous chondrocyte implantation is a good treatment option for athletic persons - Niethammer, Thomas Richard (Knee Surg Sports Traumatol Arthrosc, 2020)
PURPOSE: Autologous chondrocyte implantation is an established method for the treatment of joint cartilage damage. However, to date it has not been established that autologous chondrocyte implantation is an appropriate procedure for cartilage defects therapy in athletic persons. The aim of this study is to analyze if third-generation autologous chondrocyte implantation is an appropriate treatment for athletic persons with full cartilage defect of the knee joints. METHODS: A total of 84 patients were treated with third-generation autologous chondrocyte implantation (NOVOCART(®) 3D). The mean follow-up time was 8 years (5–14). Sports activity was measured via UCLA Activity Score and Tegner Activity Scale before the onset of knee pain and postoperatively in an annual clinical evaluation. 41 athletic persons and 43 non-athletic persons (UCLA-Cut-off: 7; Tegner Activity Scale-Cut-off: 4) were analyzed. Patient reported outcomes were captured using IKDC subjective, KOOS, Lysholm score and VAS score on movement. RESULTS: Patient reported outcomes (IKDC, VAS at rest, VAS on movement) showed significant improvement (p < 0.001) postoperatively. Athletic persons demonstrated significantly better results than non-athletic persons in the analyzed outcome scores (IKDC: p < 0.01, KOOS: p < 0.01, Lysholm score: p < 0.01). 96.4% of the patients were able to return to sport and over 50% returned or surpassed their preinjury sports level. The remaining patients were downgraded by a median of two points on the UCLA- and 2.5 on the Tegner Activity Scale. A shift from high-impact sports to active events and moderate or mild activities was found. Furthermore, it was shown that preoperative UCLA score and Tegner Activity Scale correlated significantly with the patient reported outcome postoperatively. CONCLUSION: Autologous chondrocyte implantation is a suitable treatment option for athletic persons with full-thickness cartilage defects in the knee. The return to sports activity is possible, but includes a shift from high-impact sports to less strenuous activities.